2002
DOI: 10.1103/physrevb.65.094433
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-assisted atomic-level engineering of spin valves

Abstract: Surfactant Ag is successfully used to atomically engineer interfaces and nanostructure in NiO-Co-Cu-based bottom spin valves. At a Cu spacer thickness of 1.5 nm, a strong net ferromagnetic ͑or positive͒ coupling Ͼ13.92 kA/m ͑Ͼ175 Oe͒ between NiO-pinned and ''free'' Co layers leads to a negligible ''giant'' magnetoresistance ͑GMR͒ effect ͑Ͻ0.7%͒ in Ag-free samples. In contrast, the net ferromagnetic coupling could be reduced by a factor of 2 or more in spin valves deposited in the presence of Ϸ1-3 ML of surfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…It has been demonstrated in the literature that by using surfactants, the problem of asymmetric interfaces can be reduced to a large extent [16][17][18][19][20][21][22]. The prerequisites for a material to qualify as a surfactant is its optimal quantity and a low as compared to other elements present in the multilayer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in the literature that by using surfactants, the problem of asymmetric interfaces can be reduced to a large extent [16][17][18][19][20][21][22]. The prerequisites for a material to qualify as a surfactant is its optimal quantity and a low as compared to other elements present in the multilayer.…”
Section: Introductionmentioning
confidence: 99%
“…Several other surfactant elements such as Bi, [26][27][28][29][30] Ag, [31][32][33][34][35] Au 36 and In 37 have been similarly found to induce layer quality improvement for physically deposited multilayers.…”
Section: D332mentioning
confidence: 99%
“…[31][32][33][34] The growth mechanisms induced by Ag as a surfactant in GMR multilayers were investigated by An et al 35 by using interface-sensitive X-ray anomalous scattering techniques. These results also suggested that the addition of Ag during deposition suppresses interfacial intermixing.…”
Section: D332mentioning
confidence: 99%
“…[10] Silver has been used a surfactant in the deposition of giant magnetoresistive (GMR) spin valves. [11,12] The GMR spin valve structure generally consists of a magnetic transition metal layer, such as Co, Ni, or Fe, and a layer of a noble metal, such as Au. The transition metals agglomerate as they are deposited on the noble metal layer, unless a surfactant is used.…”
Section: Introductionmentioning
confidence: 99%
“…An order of magnitude increase was reported in the GMR properties of a NiO-Co-Cu-Co structure with the incorporation of silver as a surfactant in the manufacturing process. [12] Generally, depositing elemental materials by ALD is challenging due to the lack of a broadly applicable reducing agent allowing the saturative exchange-type reactions for ALD of compound films. For example, copper deposition has been attempted with several reducing agents, elemental zinc, [13] alcohols, [14,15] and molecular hydrogen, [16][17][18][19][20] but none of them has proven to be a good all-round solution.…”
Section: Introductionmentioning
confidence: 99%